The Ethio-Eritrea border war: struggle for territorial integrity or politico-economic supremacy?. Issue 1 (2nd January 2021) - Malk, Bahlbi Y.
ABSTRACT: The Ethio-Eritrea border war, which took place from 1998–2000, was not formally resolved until the signing of a peace declaration on 9 July 2018. Known as a 'fight between two bald men over a comb', this conflict has long puzzled social scientists and political analysts. While the two countries provided different explanations for the conflict to rally public support and justify the price of war, the author argues that the conflict exceeded the logics of territorial integrity. Rather, he contends that given the colonial legacy of intentionally instituting borders to divide communities and ethnic groups, it is not possible to fully understand the border dispute without accounting for the transnational nature of the ruling ethnic groups. This is because the border and ethnic conflicts that have characterised post-colonial Africa have usually been linked to the creation of inter-ethnic groups, intra-ethnic competition and artificial boundaries between neighbouring nation-states. The Ethio-Eritrea border dispute is best understood through the lens of an ethno-linguistic struggle for supremacy disguised as a patriotic campaign against invaders. The paper concludes by reflecting on the durability of the 2018 peace declaration.